2019
DOI: 10.1039/c9cc01018a
|View full text |Cite
|
Sign up to set email alerts
|

An Sn doped 1T–2H MoS2 few-layer structure embedded in N/P co-doped bio-carbon for high performance sodium-ion batteries

Abstract: A facile route for fabrication of an Sn doped 1T–2H MoS2 few-layer structure embedded in N/P co-doped bio-carbon is initially developed using natural chlorella as an adsorbent and a nanoreactor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…[59][60][61] In addition, the abundant nitrogen and phosphorus elements in the protein of chlorella are capable of transforming in situ to give N, Pc o-doping in the bio-carbon during the calcination process, whicht ailors the electric structures furthert oe levatet he conductivity of the electrode materials. [62][63][64][65] All of these findings prompted us to design MoSe 2 -based heteroatoms-dopedc arbon nanocomposites by using the chlorella as precursor and adsorbent. Notably,t od ate, constructing ultra-fine few-layer MoSe 2 nanostructures embedded in N, Pc o-doped bio-derived carbon hybridsa st he electrode materials for SIBs/PIBs are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…[59][60][61] In addition, the abundant nitrogen and phosphorus elements in the protein of chlorella are capable of transforming in situ to give N, Pc o-doping in the bio-carbon during the calcination process, whicht ailors the electric structures furthert oe levatet he conductivity of the electrode materials. [62][63][64][65] All of these findings prompted us to design MoSe 2 -based heteroatoms-dopedc arbon nanocomposites by using the chlorella as precursor and adsorbent. Notably,t od ate, constructing ultra-fine few-layer MoSe 2 nanostructures embedded in N, Pc o-doped bio-derived carbon hybridsa st he electrode materials for SIBs/PIBs are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the optimized N,S co-doped CNFs can induce numerous extrinsic defects and active sites, which can further enhance the sodium absorption properties [35]. In comparison, the Sn/N-CNFs, Sn/NS-CNFs, and Sn/N-CNFs@rGO electrodes deliver a relatively lower (1) 4Sn + 15Na + ↔ Na 15 Sn 4 (2) xC + Na + + e − ↔ NaC x capacity of 201, 300, and 410 mAh g −1 after 200 cycles at 100 mA g −1 , respectively. It can be concluded that the capacity retention and cycling performance upgrade in the order Sn/N-CNFs < Sn/NS-CNFs < Sn/N-CNFs@rGO < Sn/ NS-CNFs@rGO, and also demonstrate that S doping and rGO wrapped can further improve the Na + storage properties [51].…”
Section: Resultsmentioning
confidence: 99%
“…Rechargeable sodium-ion batteries (SIBs) have attracted increasing attention for large-scale energy storage in renewable energy and smart grid applications, owing to their favorable energy density, natural abundance, and low cost [1][2][3][4][5]. However, the larger size of Na + (1.02 Å in radius) vs. Li + (0.76 Å in radius) leads to sluggish diffusion kinetics as well as large volume changes during sodiation/desodiation process, which results in poor cycling stability and inferior rate capability [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) layered transition metal dichalcogenides have attracted widespread attention for applications in energy storage due to their high capacity and safer working potential [9][10][11] . Among various LTMDs (i.e., MoS 2 , WS 2 , ReS 2 , WSe 2 and TiS 2 ) [12][13][14][15] , VS 2 has the typical metallic property. Its V layers and S layers are bonded together by weak van der Waals interaction, and V layers are sandwiched by two S layers thus forming a three-layer structure of S-V-S [16,17] .…”
Section: Introductionmentioning
confidence: 99%